REPRESENTING EDUCATIONAL VALUES IN BUTON FOLKTALES THROUGH INTERTEXTUALITY: DEVELOPING ORAL LITERATURE LEARNING RESOURCES FOR ELEMENTARY SCHOOL STUDENTS - Muhammad Yusnan; Isaac John Ibanga; Munirah Munirah; Erniati Erniati; Agusalim Agusalim (Universitas Labuhanbatu, 2026)
Purpose – This study aims to identify educational values embedded in Buton folktales through an intertextuality approach and develop valid, practical, and effective oral literature learning resources for elementary school students.Methodology – This Research and Development (R&D) study adopted the ADDIE model involving 177 elementary school students from seven public schools in Baubau City, Indonesia. Data were collected through document analysis, observations, expert validation, questionnaires, and pre-test/post-test assessments. Qualitative data were analyzed thematically, while quantitative data were examined using descriptive statistics and a Paired Sample t-test.Findings – Six educational values were consistently identified: religiosity, honesty, responsibility, social responsibility, leadership, and cultural preservation. The developed learning resources achieved a very high validity score (4.77) and demonstrated excellent practicality, as indicated by teacher and student responses. Students' mean scores improved from 64.28 to 86.91, with an N-Gain of 0.63 (moderate) and a significant difference between pre-test and post-test results (p < 0.001), demonstrating the effectiveness of the learning resources.Contribution – This study extends intertextuality into culturally responsive elementary education. It provides an innovative oral literature resource that integrates local wisdom, character education, and cultural literacy while supporting the preservation of Indonesia's intangible cultural heritage.